Contextual Teaching and Learning Methods in Islamic Religious Education at Lebong State Special School 1 - Endia Aprilia Sari; Desi Firmasari; Lety Febriana; Dedy Novriadi; Syukri Amin (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study investigates the application of the Contextual Teaching and Learning (CTL) approach to Islamic Religious Education instruction at State Special School 1 Lebong, with a focus on how contextual strategies can bridge the gap between religious material and the real experiences of students with special needs. The research methodology adopts a qualitative paradigm with a descriptive-interpretive design. Triangulation data gathering methods include academic documentation reviews, in-depth interviews with educational stakeholders, and structured participatory observation. To produce accurate and trustworthy results, data analysis employs Miles and Huberman's interactive model, which comprises the phases of data reduction, data presentation, and conclusion drafting. The study's conclusions showed that the CTL approach in Islamic Religious Education (PAI) instruction at SLBN 1 Lebong was operationalized through seven fundamental pillars: constructivism, investigation, and questioning, learning community, modeling, reflection, and authentic assessment. Teachers designed learning differentiation by adjusting the complexity of the material, utilizing multisensory media, and providing individual scaffolding that was responsive to the specific characteristics and obstacles of each student. Significant findings indicate that the CTL approach not only improved students' cognitive competence in understanding fundamental concepts of Islamic teachings but also optimized their active involvement in the learning process.